Experiment on Recovery of Hydrogen Isotopes from Li17Pb83 Blanket by Liquid-Gas Contact. (19th May 2017) - Kinjo, M.; Fukada, S.; Katayama, K.; Edao, Y.; Hayashi, T.
Abstract: Recovery of hydrogen dissolved in Li-Pb eutectic alloy by mean of a bubbling tower is experimentally investigated. Mass-transfer coefficients to predict tritium recovery rate are experimentally determined when Ar and Ar+H2 gas bubbles are injected into Li-Pb through an I-shaped nozzle under the conditions of temperature 573–773 K and H2 partial pressure of 1 Pa–0.1 MPa. The results are fitted by an analytical equation based on diffusion and solution in Li-Pb. So that, the rate-determining step is hydrogen diffusion through a boundary layer formed in Li-Pb-gas interface and absorption and desorption are found to be almost reversible.